Hubungan Konsumsi Makanan Cepat Saji (Fast Food) Dengan Kejadian Dismenore Pada Remaja Putri Di SMA Negeri 6 Madiun - Randra, Devita Ivania; Puspitasari, Dyah Intan; Setyaningrum, Zulia (Universitas Tadulako, 2025)
Dysmenorrhea is one of the most common menstrual disorders among adolescent girls, often affecting their learning activities and quality of life. One factor suspected to be associated with dysmenorrhea is dietary habits, particularly the frequent consumption of fast food, which is high in fat, sodium, and low in fiber. This study aims to determine the relationship between fast food consumption and the incidence of dysmenorrhea among female students at SMA Negeri 6 Madiun. This study employs a descriptive-analytic method with a cross-sectional approach to explain the relationship between fast food consumption and the occurrence of dysmenorrhea experienced by female adolescents at SMA Negeri 6 Madiun.. The population consisted of all female students at SMA Negeri 6 Madiun, with samples selected through simple random sampling. The results showed that most of the respondents frequently consumed fast food (51.3%) and experienced moderate dysmenorrhea (40.4%). The statistical test results from 154 female adolescents at SMA Negeri 6 Madiun show that a portion of the respondents (55.0%) experienced a significant relationship between fast-food consumption and the occurrence of dysmenorrhea (P value = 0.000 < 0.05). It can be concluded that the more frequently adolescents consume fast food, the higher their risk of experiencing dysmenorrhea. This study is expected to serve as a basis for nutrition education and reproductive health promotion efforts within the school environment.